Self-expanding apical closure device for full-percutaneous closed-chest transapical valve procedures with large-sized introducer sheaths: first study in an animal model. (1st August 2019) - Hong, Nanchao; Lu, Yanan; Hu, Hanbo; Sun, Jing; Sun, Kun; von Segesser, Ludwig Karl; Berdajs, Denis; Chen, Sun; Ferrari, Enrico
Abstract: OBJECTIVES: Available apical occluders do not fulfil requirements for full-percutaneous transapical valve procedures with large-sized introducer sheaths. A self-expanding closure device designed for closed-chest transapical valve procedures was tested in an animal model to verify safety, efficacy and thrombogenicity. METHODS: Large-sized 21-Fr introducer sheaths (Certitude™ system for Sapien™ valves) were percutaneously placed in the ventricles of nine 3-month old minipigs. To seal the apical access, delivery catheters carrying folded self-expanding plugs were inserted. Then, the plugs were deployed while sheaths were removed. Echocardiograms verified tamponade and cardiac function, drains were not placed and a 3-month long aspirin therapy was administered. After 6 and 9 months, animals were euthanized and organs were analysed for macroembolic lesions search. Histological analysis was also performed. RESULTS: Nine minipigs (weight: 28±3 kg) were used for this study. Eight plugs were successfully deployed in 8 ventricles without cardiac tamponade or ventricular dysfunction (success rate: 88.9%). In a failed procedure (the animal died after 1 month of cardiac tamponade), the outer disc of the apical plug got stuck in the intercostal space and did not correctly deploy. Post-mortem analysis in 8 minipigs at 6 ( n  = 4) and 9 months ( n  = 4) confirmed full deployment and good fixation of all plugs with internal surfaces covered by new endocardium. Macroscopic analysis of myocardium and vital organs showed absence of embolic lesions. Histological analysis showed absence of significant inflammatory infiltration and thrombosis. CONCLUSIONS: In this animal model, self-expanding closure devices sealed 21-Fr large percutaneous apical accesses without acute tamponade, thrombosis or embolization. Further tests to evaluate full-percutaneous closed-chest apical procedures are required.